1992
DOI: 10.1002/pros.2990200205
|View full text |Cite
|
Sign up to set email alerts
|

Prostate specific antigen and prostatitis I. Effect of prostatitis on serum psa in the human and nonhuman primate

Abstract: Prostate specific antigen (PSA) has become a mainstay in the diagnosis and management of patients with prostate cancer. We have found, as have others, that it may be elevated in patients with prostatic inflammation. Ten patients had clinical evidence of prostatitis and elevated PSA levels. Six of these had persistently elevated levels after antibiotic treatment. After transrectal ultrasonography and biopsy, two had findings of adenocarcinoma, and the rest had a pathologic diagnosis of acute or chronic prostati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
5

Year Published

1996
1996
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(65 citation statements)
references
References 9 publications
2
58
0
5
Order By: Relevance
“…The observed di erence found in seminal plasma PSA concentration, however, is unlikely to be explained by storage, as the handling of samples were identical in the two groups. Serum PSA concentration increases in patients with urinary retention, lower urinary tract infections, and prostatitis, 22,23 conditions frequently present in patients with SCI. The impact of these conditions on seminal plasma PSA has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…The observed di erence found in seminal plasma PSA concentration, however, is unlikely to be explained by storage, as the handling of samples were identical in the two groups. Serum PSA concentration increases in patients with urinary retention, lower urinary tract infections, and prostatitis, 22,23 conditions frequently present in patients with SCI. The impact of these conditions on seminal plasma PSA has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,12 However, many studies have shown that inflammation is a factor that must be considered in prostate cancer screening studies, as it increases PSA values. 5,6,10,13 In 1995, Nadler et al 5 found in their series, in which they compared 147 patients without clinical prostatitis and with high PSA values to 64 patients with normal PSA values, that acute and chronic prostatitis was related to the increase in PSA.…”
Section: Commentmentioning
confidence: 99%
“…3 Acute prostatitis is one of the well-established causes of PSA elevation. 4 Moreover, in many of the biopsybased studies, it has been reported that prostate inflammation is related to elevated PSA. [5][6][7] In addition, it has been shown that biopsy can be avoided following antibiotics therapy in many patients in whom inflammation was found in the prostatic secretion in the PSA gray zone.…”
Section: Introductionmentioning
confidence: 99%
“…1 Many experimental and clinical studies suggest a correlation between acute and chronic prostatitis and increased serum PSA levels. [2][3][4][5][6] Subclinical inflammation of the prostate could elevate serum PSA in asymptomatic patients without clinically detectable prostate cancer. Gerstenbluth et al, 7 in 2002, reported chronic prostatitis as a common finding in radical prostatectomy specimens.…”
Section: Introductionmentioning
confidence: 99%